INTERACTIVE READING ACTIVITIES BY USING KNOW, WANT, AND LEARN STRATEGY: A DESCRIPTIVE STUDY - Ayu Mardhotillah; Nurul Hasanah Fajaria (Lingua, 2021)
The objectives of this research are (1) To identify whether or not KWL strategy with Prezi can implemented in student’s reading activities; (2) To describe the students respond toward the student’s reading activities through the implementation of KWL strategy with Prezi. Six eighth grade students from SMP N 27 Kota Bekasi in the 2020/2021 academic year will participate in this study who were taken by using purposive sampling. This research uses a descriptive qualitative method. Meanwhile, in this study, the data collection used observations and interviews. The researcher uses contextualization and codification to analyze the data. The result from the research that has been carried out are (1) The implementation of KWL strategy with Prezi can help the students’ reading activities for the middle grade students of SMP Negeri 27 Kota Bekasi in the academic year of 2020/2021; (2) Based on the finding from the observation and interview, some students interesting with this strategy because they can use this strategy for the answer the question of reading assignment in their school later. The students enjoy the reading activities that has been presented interestingly through Prezi and they feel more helpful with every step from KWL strategy.